Toward Understanding the Effects of Visual and Tactile Stimuli to Reduce the Sensation of Movement with XR Mobility Platform - Sawabe, Taishi; Kanbara, Masayuki; Fujimoto, Yuichiro; Kato, Hirokazu (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
This paper investigates a reduction method for passenger's movement sensation with the XR mobility platform mounted on an autonomous vehicle to improve passenger comfort during auto-driving. We investigate a reduction method that controls passenger's sense of movement by controlling visual and tactile perception using a multimodal XR mobility platform which consists of an immersive display and a motion platform with a tilting seat. The result of 30 subjects shows the sense of movement perceived by the passenger was reduced significantly when both visual acceleration and tactile acceleration control method was activated inside a moving autonomous vehicle.